Experimental Analysis and Improvements of a Visible Spectrophotometer for Detection of Nano Materials - Pamula Rajakumari; Polaiah Bojja; Smitha Chowdary Ch; Sunkara Teena Mrudula; Krishnam Raju Putta; Amsalu Gosuadigo (International Journal of Chemical Engineering)
As the field of nanotechnology advances, there is an increasing need for green nanomaterial identification devices. Recently, a few new studies have reminded us that as nanotechnology gets better and better, so will natural phenomena. As we grow closer to and finally reach the nanoscale, it is feasible that new physical expertise will develop. Developments in the future may allow for new technical advancements. It is the ability of nanotechnology to construct human constructs at the nanoscale that distinguishes it from other fields of science and engineering. Various components, including high-dissociation electron microscopy, centre-ion beam milling tools, and scanner probes, have made this practical. Spectrometers, sometimes known as spectrometers, are used in fabric identification machines. To conclude this inquiry, a nanoparticle scatter spectrometer was devised and built artificially. This study focused on the visible spectrum of spectroscopy because there are a broad number of programmes available for visible optical instruments.